Efektivitas Aplikasi Gamifikasi dalam Meningkatkan Pengetahuan Remaja Tentang Stunting - Asep Paturohman; Roma Tao Toba Muara Ria; Solaeman Solaeman; Agustina Gea (Jurnal Ners, 2026)
One of the nutritional problems faced by many developing countries is Stunting. This occurs when children's growth is hampered due to chronic malnutrition. Gamafikasi is a game application created for education. The game application in this study is named Stunting Defender, the purpose of this study is to test the effectiveness of Stunting gamafikasi on adolescent knowledge about stunting. The method used is a simple quantitative experiment that compares the average value of the pre-test and post-test points, the sample used is 20 junior high school students. The results of the study found that more than half of the gender is 13 people or 65% male. The total age of 20 respondents or 100% is 11-14 years old, the pretest score for knowledge is more than half either 75% or 15 respondents, the posttest score is almost entirely 95% or 19 respondents have good knowledge. The average pre-test score was 56.2 points and the average post-test score was 78.9 points, indicating a 22.7-point increase in knowledge. Statistical testing yielded a p-value of 0.042, indicating a significant difference in knowledge before and after playing the Stunting Defender game.